Synthesis, characterization and screening of anti convulsant activity of novel tetra substituted imidazole derivatives - Lincy Joseph; Akshay Murali; Mathew George (International Journal of Pharmacy and Analytical Research, 2022)
In this study a new tetra substituted imidazole derivatives has been synthesized from the condensation of Benzil, substituted aldehyde, substituted aromatic amine and ammonium acetate in presence of glacial acetic acid at 120 -140 ºC. The newly synthesized derivatives has been characterized by various physicochemical techniques such as melting point, TLC, FTIR 1HNMR, and elemental analysis. The synthesized compounds are screened for their anti convulsant activity by PTZ induced convulsion and MES method. The standards used for the method are diazepam and phenytoin respectively.